2019
DOI: 10.1016/j.prrv.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary dysplasia: Pathophysiology and potential anti-inflammatory therapies

Abstract: Inflammation of the preterm lungs is key to the pathogenesis of bronchopulmonary dysplasia (BPD), whether it arises as a consequence of intrauterine inflammation or postnatal respiratory management. This review explores steroidal and non-steroidal therapies for reducing neonatal pulmonary inflammation, aimed at treating or preventing BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 132 publications
(150 reference statements)
1
31
0
1
Order By: Relevance
“…The effect of corticosteroids on hastening weaning from mechanical ventilation had been reported in preterms with BPD in neonatal intensive care units, but not in older infants with BPD aged more than 3 months 11 . The improvements observed after the start of high‐dose IV methylprednisolone in these two infants aged 6 and 7 months advocates for a persisting lung inflammation linked to their severe BPD and acutely exacerbated by mechanical ventilation, that was counteracted by this anti‐inflammatory treatment 17 . Two of the three infants who required chronic NIV in our study also seemed to improve after the IV pulses of methylprednisolone.…”
Section: Discussionmentioning
confidence: 92%
“…The effect of corticosteroids on hastening weaning from mechanical ventilation had been reported in preterms with BPD in neonatal intensive care units, but not in older infants with BPD aged more than 3 months 11 . The improvements observed after the start of high‐dose IV methylprednisolone in these two infants aged 6 and 7 months advocates for a persisting lung inflammation linked to their severe BPD and acutely exacerbated by mechanical ventilation, that was counteracted by this anti‐inflammatory treatment 17 . Two of the three infants who required chronic NIV in our study also seemed to improve after the IV pulses of methylprednisolone.…”
Section: Discussionmentioning
confidence: 92%
“…Another investigation of 192 newborns found that lung infections in early newborns (particularly in the first 3 days of life) were related to the evolution of chronic lung disease (46). Under a combined effect of other BPD risk factors such as hyperoxia and mechanical ventilation, infection triggers a series of pro-inflammatory substances, such as IL-1β, IL-6, IL-8, NLRP3, TNF-α, and collagen I, which are further regulated by infiltrating neutrophils and macrophages (47)(48)(49). These inflammatory mediators in immature lungs of premature infants restrict the activity of surfactant proteins and the vascular endothelial growth factor (49), contributing to the development of alveolar and vascular alterations and other characteristic pathologies in BPD.…”
Section: Infection/inflammationmentioning
confidence: 99%
“…These inflammatory mediators in immature lungs of premature infants restrict the activity of surfactant proteins and the vascular endothelial growth factor (49), contributing to the development of alveolar and vascular alterations and other characteristic pathologies in BPD. Furthermore, TLR binding-induced reactive oxygen species (ROS) activate the NLRP3/caspase-1 pathway, which promotes IL-1b production (47), amplifying the inflammation process.…”
Section: Infection/inflammationmentioning
confidence: 99%
“…An additional complication of preterm birth is abnormal lung development. Bronchopulmonary dysplasia (BPD) is a chronic lung disease characterized by inflammation and arrest of alveolar development that affects 30-60% of infants born preterm [125][126][127][128]. Studies suggest that part of the oxidative and mechanical damage is the result of respiratory ventilation [129].…”
Section: Alterations In the Immune System And Epithelial Barrier Of Tmentioning
confidence: 99%